Case Report: Interferon-γ Restores Monocytic Human Leukocyte Antigen Receptor (mHLA-DR) in Severe COVID-19 With Acquired Immunosuppression Syndrome - Dickel, Steffen; Grimm, Clemens; Amschler, Katharina; Schnitzler, Sebastian Uwe; Schanz, Julie; Moerer, Onnen; Payen, Didier; Tampe, Bjoern; Winkler, Martin Sebastian (Frontiers in Immunology, 2021)
Background: The major histocompatibility complex (MHC) class II characterized by monocytes CD14+ expression of human leukocyte antigen receptors (HLA-DR), is essential for the synapse between innate and adaptive immune response in infectious disease. Its reduced expression is associated with a high risk of secondary infections in septic patients and can be safely corrected by Interferon-y (IFNy) injection. Coronavirus disease (COVID-19) disease induces an alteration of Interferon (IFN) genes expression potentially responsible for the observed low HLA-DR expression in circulating monocytes (mHLA-DR). Methods: We report a case of one-time INFy injection (100mcg s.c.) in a superinfected 61-year-old man with COVID-19 associated acute respiratory distress syndrome (ARDS), with monitoring of mHLA-DR expression and clinical tolerance. Observations: Low mHLA-DR pretreatment expression (26.7%) was observed. IFNy therapy leading to a rapid increase in mHLA-DR expression (83.1%). Conclusion: Severe ARDS in a COVID-19 patient has a deep reduction in mHLA-DR expression concomitantly with secondary infections. The unique IFNy injection was safe and led to a sharp increase in the expression of mHLA-DR. Based on immune and infection monitoring, more cases of severe COVID-19 patients with low mHLA-DR should be treated by IFNγ to test the clinical effectiveness.